Simple current sensor fault‐tolerant control strategy for switched reluctance motors in high‐reliability applications - Nasir Ali; Qiang Gao (IET Electric Power Applications, 2021)
Abstract Switched reluctance motors (SRMs) are considered as a potential candidate in many high‐reliability demanding applications, including electrical vehicles (EVs), hybrid EVs and more electric aircrafts. For precise and stable control performance, normally an SRM drive requires one current sensor for each phase winding. Failure of any of these sensors will inevitably degrade the system's performance. The behaviour of an SRM drive under current sensor failure is investigated and a fault‐tolerant control technique is proposed by changing the current sensor installation scheme without adding extra current sensors. Moreover, through the analysis of the detected currents by the phase current sensors and the dc‐link sensor, a diagnostic scheme for current sensors failure is presented. The excitation current in the faulty phase under postfault conditions is reconstructed through a simple calculation without injecting a high‐frequency signal or modifying the switching signals, thereby reducing the current distortion and avoiding voltage penalty issues. Motor drive can operate with satisfactory control performance even when all the phase current sensors are in fault conditions. Detailed analysis under both steady state and dynamic conditions through thorough simulations and experiments has been carried out on a three‐phase 12/8 SRM. The extensive results validate the effectiveness of the proposed technique.